IMPLEMENTASI KURIKULUM MUATAN LOKAL TILAWAH DAN TAHFHIZUL QUR’AN DALAM MENINGKATKAN HASIL PEMBELAJARAN AL-QUR’AN HADITS DI PPMTI BAYUR AGAM - Mulia, Elvira (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2022)
The curriculum is a set of plans and arrangements regarding the objectives, content and teaching materials as well as the methods used as guidelines for the implementation of learning activities to achieve certain goals. Local content is part of the structure and content of the curriculum contained in the Content Standards in the curriculum at the education unit level. By applying the local content curriculum Tilawah and Tahfidzul Qur'an, the students' learning value of Al-Qur'an Hadith is achieved at school. In fact, there are still many students who have not been able to memorize the Qur'an properly and correctly, especially understanding Recitation and Tahfidzul Qur'an, but in learning the Qur'an, Hadith is still weak. In this study, researchers used qualitative methods. This study discusses how the Implementation of Local Content Curriculum Recitation and Tahfidzul Qur'an in Improving Learning Outcomes of Al-Qur'an Hadith at PPMTI Bayur, Tanjung Raya District, Agam Regency. So that in the application of the existing local content of Tilawah and Tahfidzul Qur'an it can help the value of learning Al-Qur'an Hadith for students at PPMTI Bayur. The Tahfidz program in local content subjects here is one of the graduation requirements for PPMTI Bayur students.